Polisemi dan Ambiguitas pada Konten Instagram @Tempodotco serta Pemanfaatannya sebagai Bahan Ajar Alternatif Semantik - Yazid Rizki; Erwan Kustriono (Yayasan Al-Afif, 2026)
This study examines the phenomenon of polysemy and ambiguity in posts on the Instagram account @Tempodotco and its potential use as alternative teaching material. The problem focuses on identifying forms of polysemy and ambiguity in digital news texts and exploring their educational value for semantic learning. The purpose of this study is to describe the use of polysemy and ambiguity and to design a model for their use as teaching materials for 10th grade students. The method used is descriptive qualitative with content analysis techniques on posts from February 2025. The results show that polysemy and ambiguity appear in various forms, such as lexical and metaphorical polysemy and structural ambiguity, which function as discourse strategies to attract attention and convey social criticism. This analysis produced a number of authentic examples that can be integrated into Indonesian language learning materials to train students' semantic analysis and critical media literacy skills. The impact of this research provides a practical contribution in the form of alternative contextual teaching materials that improve students' understanding of double meanings in digital media texts. In conclusion, @Tempodotco content can be used as a relevant learning resource to develop students' language competence and digital literacy skills.